Effect of chitosan/starch aldehyde‐catechin conjugate composite coating on the quality and shelf life of fresh pork loins. (1st April 2022) - Hu, Huixia; Yong, Huimin; Zong, Shuai; Jin, Changhai; Liu, Jun
Abstract: BACKGROUND: Fresh pork is susceptible to oxidation and spoilage. Edible coating containing antioxidant and antimicrobial agents can create moisture and oxygen barriers around pork and inhibit oxidation and microbial growth in the pork. In this study, chitosan in combination with starch aldehyde‐catechin conjugate (SACC) was used as a novel edible coating material for preserving fresh pork loins at chilled storage (4 ± 1 °C) for 14 days. Effect of chitosan/SACC composite coating on the quality of pork loins including weight loss, colour, pH value, microbial spoilage, lipid oxidation, protein oxidation, texture and sensory attributes during chilled storage was determined. RESULTS: Chitosan and SACC had synergistic antioxidant and antimicrobial actions. As compared with uncoated and chitosan coated pork loins, chitosan/SACC coated pork loins showed lower weight loss (7.16%), pH value (5.99), total viable count (7.11 log CFU g −1 ), total volatile base nitrogen content (130.2 mg kg −1 ), lipid oxidation level (0.47 mg malondialdehyde kg −1 ), protein oxidation level (0.047 mmol free thiol group g −1 ) and shear force (27.40 N) on day 14. Meanwhile, chitosan/SACC composite coating effectively maintained the colour, micro‐structure and sensory attributes of pork loins throughout chilled storage period. The shelf life of pork loins was extended from 8 days (uncoated samples) to 14 days by chitosan/SACC composite coating. CONCLUSION: Chitosan/SACC composite coating effectively retarded the oxidation and spoilage of pork loins during chilled storage. © 2022 Society of Chemical Industry.